Chemical bath deposition of h-MoO3 on optical fibre as room-temperature ammonia gas sensor - Wen, Hong Chua; Yaacob, Mohd Hanif; Tan, Chou Yong; Ong, Boon Hoong (Elsevier, 2021)
This study successfully developed a semiconductor metal oxide-based ammonia gas sensor that was powered by an Ultraviolet–Visible-near-IR optical light source. However, optical fibre gas sensors using single metal oxide nanomaterial are limited. To address this situation, a h-MoO3 nanorod was grown on a tapered region of optical fibre glass using a simple chemical bath deposition to form a unique sensing element. An additional annealing treatment was then performed to modify the oxidation state of h-MoO3. The property changes of the samples were characterised using different techniques, such as FESEM, TEM, XRD, XPS, TGA and UV–Vis. Overall, the annealing treatment improved the sensitivity performance, response and recovery time of the sensor towards NH3. h-MoO3 that was annealed at 150 °C in air showed stable room temperature absorbance responses of 0.05, 0.18, 0.22, 0.28 and 0.35, a fast response time of 210 s towards 500 ppm of NH3 and strong stability and repeatability. The optical NH3 gas-sensing behaviour was significantly correlated with the non-stoichiometric Mo5+ content. The chemisorbed oxygen species and physiosorbed NH3 altered the refractive index and its absorption coefficient on the nanorod, which manipulated the optical signal and acts as a sensing mechanism. These results verify that a chemical bath deposition growth of the h-MoO3 nanorod exhibits a promising optical sensing characteristic, which paves a path for emerging gas-sensing technology.